Different Risk Factors for Early and Late Colorectal Anastomotic Leakage in a Nationwide Audit. Issue 11 (November 2018) - Sparreboom, Cloë L.; van Groningen, Julia T.; Lingsma, Hester F.; Wouters, Michel W.J.M.; Menon, Anand G.; Kleinrensink, Gert-Jan; Jeekel, Johannes; Lange, Johan F.
Abstract : BACKGROUND: Anastomotic leakage remains a major complication after surgery for colorectal carcinoma, but its origin is still unknown. Our hypothesis was that early anastomotic leakage is mostly related to technical failure of the anastomosis, and that late anastomotic leakage is mostly related to healing deficiencies. OBJECTIVE: The aim of this study was to assess differences in risk factors for early and late anastomotic leakage. DESIGN: This was a retrospective cohort study. Settings: The Dutch ColoRectal Audit is a nationwide project that collects information on all Dutch patients undergoing surgery for colorectal cancer. PATIENTS: All patients undergoing surgical resection for colorectal cancer in the Netherlands between 2011 and 2015 were included. MAIN OUTCOME MEASURES: Late anastomotic leakage was defined as anastomotic leakage leading to reintervention later than 6 days postoperatively. RESULTS: In total, 36, 929 patients were included; early anastomotic leakage occurred in 863 (2.3%) patients, and late anastomotic leakage occurred in 674 (1.8%) patients. From a multivariable multinomial logistic regression model, independent predictors of early anastomotic leakage relative to no anastomotic leakage and late anastomotic leakage relative to no anastomotic leakage included male sex (OR, 1.8; p < 0.001 and OR, 1.2; p = 0.013) and rectal cancer (OR, 2.1; p < 0.001 and OR, 1.6; p = 0.046). Additional independent predictors of early anastomotic leakage relative to no anastomotic leakage included BMI (OR, 1.1; p = 0.001), laparoscopy (OR, 1.2; p = 0.019), emergency surgery (OR, 1.8; p < 0.001), and no diverting ileostomy (OR, 0.3; p < 0.001). Independent predictors of late anastomotic leakage relative to no anastomotic leakage were Charlson Comorbidity Index of ≥II (OR, 1.3; p = 0.003), ASA score III to V (OR, 1.2; p = 0.030), preoperative tumor complications (OR, 1.1; p = 0.048), extensive additional resection because of tumor growth (OR, 1.7; p = 0.003), and preoperative radiation (OR, 2.0; p = 0.010). LIMITATIONS: This was an observational cohort study. CONCLUSIONS: Most risk factors for early anastomotic leakage were surgery-related factors, representing surgical difficulty, which might lead to technical failure of the anastomosis. Most risk factors for late anastomotic leakage were patient-related factors, representing the frailty of patients and tissues, which might imply healing deficiencies. SeeVideo Abstract athttp://links.lww.com/DCR/A730 .